Military intelligence in the New Zealand wars, 1845-1864 : a thesis presented in fulfilment of the requirements of the degree of Doctor of Philosophy in Defence and Strategic Studies at Massey University, Palmerston North, New Zealand - Simons, Clifford Roy (Massey University, 2012)
This thesis analyses the nature of military intelligence in the New Zealand Wars and assesses the role that it played in the outcome of the various battles and campaigns. Military intelligence has seldom been identified as a factor in the wars and this is the first major study of it. The thesis examines the way that military intelligence was used in nineteenth century colonial warfare in general, and then applies those concepts to the New Zealand situation by studying four major wars that occurred between 1845 and 1864. The thesis shows that Maori enjoyed the advantage of fighting in their own environment which meant that they were familiar with all of the features of physical geography such as: routes and tracks, the location of communities, pa and food supplies, and barriers to travel such as rivers and swamps. They were equally aware of the socio-political aspects of the area such as the tribal groupings and political allegiances. The government made little secret of its intentions and through a number of avenues including newspapers and contact with government officers. Maori resisting the government generally had a good understanding of its strategic intentions. They were also able to monitor the activities of the troops by infiltrating military camps, by observation and reconnaissance, and by the transmission of information between Maori supportive of the government and those opposing it. In consequence, Maori generally had a good military intelligence picture throughout the wars. The thesis demonstrates that the government forces, which comprised the British Army, the Royal Navy, and various militia and volunteer units, usually had a less clear military intelligence picture. The early battles of the Northern War 1845-6 indicated that the British Army had a complete lack of understanding about the physical environment of the Bay of Islands and the enemy that they were fighting. Over the course of the period studied in this thesis, a rudimentary military intelligence system developed until, by the end of the Waikato War and Tauranga Campaign of 1864, it was moderately effective. The government collected information from its own political officers in the regions, and from missionaries, settlers and pro-government Maori to establish a relatively clear idea of the terrain and the socio-political mood within Maori communities. The British Army undertook reconnaissance in a number of ways including cavalry and by river boat. The acquisition of that information allowed the military to plan its campaigns effectively. The thesis concludes that military intelligence was an important factor in the outcome of the wars that were fought in New Zealand between 1845 and 1864. It shows that the effective use of military intelligence, or indeed the absence of it, were often significant reasons for success or failure of military operations. This new appreciation of the role and effect of military intelligence provides new insights into the battles and enhances an understanding of the whole New Zealand Wars period.
Keywords: New Zealand wars; Military intelligence